Incidence of AIDS‐defining cancers and virus‐related and non‐virus‐related non‐AIDS‐defining cancers among HIV‐infected patients compared with the general population in a large health district of northern Italy, 1999–2009. Issue 8 (7th April 2013) - Calabresi, A; Ferraresi, A; Festa, A; Scarcella, C; Donato, F; Vassallo, F; Limina, RM; Castelli, F; Quiros‐Roldan, E; ,
Abstract : Objectives: The aim of the study was to investigate the incidence of AIDS‐defining cancers (ADCs) and virus‐related and non‐virus‐related non‐AIDS‐defining cancers (NADCs) in HIV‐infected patients compared with the general population, and to assess the risk factors associated with these malignancies. Methods: We performed a retrospective cohort study for the period from 1999 to 2009 of HIV‐infected patients residing in the Local Health Authority of Brescia (northern Italy). Observed cancers in patients with HIV infection were compared with expected cancers in the population living in the same area using standardized incidence ratios (SIRs). Risk factors were assessed using Poisson regression analysis. Results: A total of 5090 HIV‐infected patients were included in the study, with 32 390 person‐years of follow‐up. We recorded 416 tumours in 390 HIV‐infected patients. Two hundred of these (48.1%) were ADCs, 138 (33.2%) were non‐virus‐related NADCs and 78 (18.7%) were virus‐related NADCs. An increased risk (SIR = 4.2) of cancers overall was found in HIV‐infected patients. A large excess of ADCs (SIR = 31.0) and virus‐related NADCs (SIR = 12.3) was observed in HIV‐infected patients, while the excess risk for non‐virus‐related NADCs was small (SIR = 1.6). The highest SIRs were observed for Kaposi sarcoma among ADCs and for Hodgkin lymphoma among virus‐related NADCs. Conversely, among non‐virus‐related NADCs, SIRs for a broad range of malignancies were close to unity. In multivariate analysis, increasing age and CD4 cell count < 50 cells/μL were the only factors independently associated with all cancers. Conclusions: Among HIV‐infected people there was an excess of ADCs and also of NADCs, particularly those related to viral infections. Ageing and severe immunodeficiency were the strongest predictors.